FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN SEBELUM DAN SELAMA COVID-19 - Juandi, Juandi; Yanti, Yanti (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research is to examine the effect of liquidity (CR), leverage (DER), firm size (SIZE), and intellectual capital (VAIC) on the performance of consumer non-cyclicals sector firms before and during the COVID-19 pandemic, using 2018 and 2019 as the pre-pandemic period and 2020 and 2021 as the pandemic period. This research uses the purposive sampling method to take samples and tests its hypotheses using regression analysis and Wilcoxon signed rank test with SPSS. The results show that liquidity, firm size prior to the pandemic, and intellectual capital have a significant effect on firm performance, while firm size during the pandemic, as well as leverage does not have a significant effect. In addition, there is no difference between the average performance of firms before and during the COVID-19 pandemic. The implication of this study is the need to increase liquidity, firm size, as well as intellectual capital to increase firm performance that will subsequently signal a good prospect to investors.